Study of perceived stress and stressors among undergraduate medical students - Sethia, Renu; Sharma, Gaurav; Shekhawat, Kirti; Aacharya, Aarti; Acharya, Rekha; Meena, Ratti Ram (International Journal Of Community Medicine And Public Health, 2019)
Background: Recently there is growing concern about stress during undergraduate’s medical training. Undue stress may cause adverse health consequences and lowered academic performance. Objective of the study was to know perceived level of stress and its causes among undergraduate medical students. Methods: A cross sectional survey, using self-structured questionnaire, was conducted among 65 third year medical students. Questionnaires were related to socio-demographic profile, perceived stress scale [PSS] and 32 item list of stressors (grouped as health related, academic and psycho-social). Student’s responses were recorded on five point Likert scale. Results: Mean PSS score was 25.53±5.55 and was significantly higher for females. Psycho-social stressors occurred most frequently, followed by the academic causes. Conclusions: Medical undergraduates face high level of stress and the causes may be varied. They need more interaction, counselling and support from faculty to relieve their stress.